Impact of urban catalysts in the transformation of the Barrios Altos (1535-2015) - Rincón Rodriguez, Iris Guadalupe (2018)
The article identifies the urban catalysts located in the Barrios Altos area, in the Historical Center of Lima. These are analyzed and classified within the urban evolutionary process of the area, characterized by historical events of political, social, economic, cultural, and architectural nature, which happens in accordance with the periods of the historical-evolutionary process that confronts the city of Lima between 1535 and 2015. Within the investigation, the latter are catalogued as catalytic processes that had an impact on the transformation of the above-mentioned area. It is thus possible to identify the impact of these urban catalysts through urban growth, and how these have influenced the transformation of Barrios Altos. In addition, it allows us to offer an explanation for the particular characteristics of the area under analysis, such as the absence of a regular trace, its delimitation in terms of the evolutionary process, the symbolism that represents the area in the process of urban growth of the City of Lima and its physical-territorial conformation given the addition of the existing sub-barrios.